Modeling high pressure flow through an orifice with real gas effects - Dall, Weston, author; Troxell, Wade, advisor; Fankell, Doug, committee member; Eftekhari Shahroudi, Kamran, committee member (Colorado State University. Libraries, 2025)
Mass flow control of compressible fluids is integral to several industry sectors, including aerospace, defense, research, and energy. Control valves are a common method of mass flow control and regulate a wide variety of fluid flows, including in the food industry, chemical processing, oil and gas refinement, fuel admission to engines and turbines, pharmaceuticals, and other use cases. Currently, leading controls manufacturers commonly regulate large volume fluid flow up to around 1000 psia within 2 percent accuracy by utilizing flow prediction equations and calibration. The Isentropic Compressible Flow Equation is one commonly used method of doing this, and for this thesis is used as a baseline for current prediction methodology. In high-pressure regimes (i.e., above 1000 psia), compressible fluids begin to deviate significantly from ideal behavior due to a phenomenon known as real gas effects. This thesis seeks to answer how compressible mass flow through an orifice can be accurately characterized at pressures above 1000 psia. To do this, existing methods and their potential for inaccuracy at high pressure are examined. A more accurate method of prediction utilizing a solver and a large fluid property library is proposed and utilized in conjunction with the existing Isentropic Compressible Flow Equation (a commonly used flow equation) to understand the deviation between the two methods. Significant deviation between methods was found to exist especially among gasses with a less ideal molecular structure. Methane displays a deviation of more than 30% in real mass flow when compared to a baseline made by the Isentropic Compressible Flow Equation. Using the solver, a final method of prediction involving use of "ratio maps" combined with the existing Isentropic Compressible Flow Equation was identified as an accurate method of mass flow prediction given knowledge of the gas flow conditions. This approach shows the capability to solve the problem of predicting mass flow through orifices at pressures greater than 1000 psia. This answers the fundamental question of this thesis and has potential as a high-pressure flow modeling solution for industry and academic applications. Another significant part of the work done in this thesis involves the identification of holes in the existing knowledge of high-pressure flow prediction and regulation. This involves both a study of existing research and determination of areas in which it is not deep and developing a solution to fix the holes in existing research for mass flow prediction. The development of a potential solution allows for the identification of challenges with this strategy and possible improvements to be made on it. In this thesis, this involves mainly involves understanding the existing research done on high pressure flow and the relative lack of 1-2 percent accurate flow modelling for high pressure compressible flow in a control valve context. Solution improvements include items such as accounting for potential viscosity effects, improving the prediction of the point at which sonic flow begins, and general improvements to the tools used to make the flow calculations. The need for real test data at high pressures was also very much emphasized in the process of this thesis. Real test data would prove out the method presented here and offer final validation.
Keywords: gas; orifice; real; high; flow; pressure